2015
DOI: 10.1007/978-3-319-20346-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silicon Biosensors Employing Emerging Capture Probes

Abstract: The application of porous silicon (PSi) for biosensing was first described by Thust et al. in 1996, demonstrating a potentiometric biosensor for the detection of penicillin. However, only in the past decade PSi has established as a promising nanomaterial for label-free biosensing applications. This chapter focuses on the integration of new emerging capture probes with PSi-based biosensing schemes. An overview of natural and synthetic receptors and their advantageous characteristics for the potential applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 121 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…For antibodies, it was demonstrated that ordered orientation results in improved performance, , and a thorough study by Bonanno et al presented the impact of steric crowding on antibody immobilization. The importance of surface chemistry for antibody conjugation was also emphasized by Martin et al Aptamers are emerging as promising alternatives to antibodies in various biosensing platforms and have been introduced in recent years as capture probes in PSi biosensors. , One main advantage of aptamer-based PSi biosensors in comparison to conventional PSi-based immunosensors is the ability to easily regenerate the sensor by a short rinsing step for multiple biosensing analyses even in complex biological fluids, as was demonstrated by Urmann et al In a later study, Voelcker and co-workers utilized PSi Fabry-Pérot interferometers to compare antibody and aptamer bioreceptors for the detection of insulin. They established that the aptamer-based biosensor outperforms the antibody-based one, in terms of both the LOD (1.9 μg mL –1 [0.33 μM] and 4.3 μg mL –1 [0.74 μM], respectively) and the response time (12 and 60 min, respectively), as shown in Figure A .…”
Section: Sensitivity and Signal Enhancement Methodsmentioning
confidence: 96%
“…For antibodies, it was demonstrated that ordered orientation results in improved performance, , and a thorough study by Bonanno et al presented the impact of steric crowding on antibody immobilization. The importance of surface chemistry for antibody conjugation was also emphasized by Martin et al Aptamers are emerging as promising alternatives to antibodies in various biosensing platforms and have been introduced in recent years as capture probes in PSi biosensors. , One main advantage of aptamer-based PSi biosensors in comparison to conventional PSi-based immunosensors is the ability to easily regenerate the sensor by a short rinsing step for multiple biosensing analyses even in complex biological fluids, as was demonstrated by Urmann et al In a later study, Voelcker and co-workers utilized PSi Fabry-Pérot interferometers to compare antibody and aptamer bioreceptors for the detection of insulin. They established that the aptamer-based biosensor outperforms the antibody-based one, in terms of both the LOD (1.9 μg mL –1 [0.33 μM] and 4.3 μg mL –1 [0.74 μM], respectively) and the response time (12 and 60 min, respectively), as shown in Figure A .…”
Section: Sensitivity and Signal Enhancement Methodsmentioning
confidence: 96%
“…Antibodies are presumably the most important and prominent class of biorecognition elements [ 7 , 8 ]. In vivo, these proteins play a crucial role in the adaptive immune system of vertebrates targeting antigens, such as pathogenic microorganisms, with high affinity and specificity [ 7 , 9 ].…”
Section: Immunosensorsmentioning
confidence: 99%
“…Antibodies are presumably the most important and prominent class of biorecognition elements [ 7 , 8 ]. In vivo, these proteins play a crucial role in the adaptive immune system of vertebrates targeting antigens, such as pathogenic microorganisms, with high affinity and specificity [ 7 , 9 ]. Antibodies consist of two moieties (each containing a light and a heavy chain) bound together by disulfide bonds; this region is referred to as the hinge region (see Figure 1A ) [ 10 , 11 ].…”
Section: Immunosensorsmentioning
confidence: 99%
“…The need to detect biological analytes for applications including medical diagnostics, environmental monitoring, and food safety, is typically met by a biosensor composed of two primary components: a capture agent (also sometimes referred to as a probe molecule or bioreceptor), which specifically binds to the desired target analyte, and a transducer, which converts the binding of the target species into a measurable optical, electrochemical, thermal, or microelectromechanical signal [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Examples of specific capture agent–target analyte ‘lock and key’ interactions are antibody–antigen interactions, enzyme–substrate interactions, peptide interactions, and oligonucleotide interactions [ 8 , 9 , 10 ]. However, despite their effectiveness and well-established use in many applications, the reliance on capture agents for analyte detection can bring about several challenges.…”
Section: Introductionmentioning
confidence: 99%